DYNAMICS OF OIL PRICE, EXCHANGE RATE AND THE TRADE PERFORMANCE OF QUOTED INDUSTRIAL SECTORS AT THE ALL SECURITIES MARKET (ASEM) IN NIGERIA - Ajeigbe, Omowumi Monisola (Advances in Social Sciences Research Journal, 2022)
The study examined the dynamic interaction among oil price, exchange rate and the trading performance of quoted industrial sectors at the Nigerian stock exchange market from 1980 to 2020 used in a Panel Vector Error Correction Mechanism (PVECM) framework. Data were sourced from BP Energy Review, Central Bank of Nigeria Statistical Bulletin and Annual report of the Nigerian Stock Exchange Market. Findings showed that long run relationships were established for oil price, exchange rate and the stock market performance of the industrial sectors. The result revealed a long run negative relationship among oil price, exchange rate and the stock market performance of the industrial sector. In the absence of possibility of complete shift of the burden of oil price rise on to the consumers, the profits and dividends of companies are reduced which may result into decline in stock prices on the long run. The study suggested that variations in oil price and exchange rate are two strong macroeconomic factors which also stand as a risk factor to the performance of the Stock Exchange Market both at the aggregate market level and the disaggregated industrial sector level, therefore, government policies need to be redirected towards controlling for both the negative and positive effect of the risk factors as their impact on the Stock Exchange Market is revealing from this study.